Knowledge Interference For Advanced Experience By A House Officer (Ho) - Saleh, Nor Shela; Rosli, Mohd Shafie; Abu Bakar, Thuaibah; Md. Ali, Azlah (Journal of Social Transformation and Regional Development, 2022)
The medical cluster is a vital part of the country's infrastructure. Medical clusters are like the strength that ensures the community's well-being, both for the locals and for the leaders. The usefulness and value of house officer expertise during medical education are investigated in this study. Furthermore, the accomplishment of house officer experience will be determined by the support of knowledge they possess. This study looked at I the degree of knowledge held by house officers, (ii) the level of experience held by house officers, and (iii) the link between knowledge and experience held by house officers. Simple random sample procedures were used to send questionnaires to 80 house officers from a hospital in Johor. The results of the study were examined using descriptive and inferential statistics. The study's findings show that house officers have a high level of expertise and experience. Studies have also shown that a house officer's expertise and experience are highly connected. Knowledge is appropriate significant and expected for enhancement to comprehend the ideal experience, according to this study. Finally, this study was employed as a model for developing trainees' learning processes and medical clusters.